A multi-criteria sustainability assessment for biodiesel alternatives in Spain: Life cycle assessment normalization and weighting. (February 2021) - Fernández-Tirado, Francisca; Parra-López, Carlos; Romero-Gámez, Mercedes
Abstract: The bioenergy sector in the European Union has undergone strong growth in line with the legislative framework, with environmental, economic and social implications at global scale. In Spain, almost 100% of biodiesel is produced from food and feed crops feedstocks. First-generation biodiesel will go on being a key partial rapid solution to replace fossil fuel in transport sector. However, impacts differ significantly among the type of agricultural system, the raw materials used and their life cycle. The aim of this study is to identify the best first-generation biodiesel alternative to replace petrodiesel in transport sector in the short term in Spain. Life Cycle Assessment normalization and weighting can facilitate decision making in situations where trade-offs among impact category results do not allow choosing one preferable solution among the alternatives. A panel weighting impact approach based on expert opinions was used to assess the sustainability of three biodiesel production systems. The results indicate that, according to expert's opinion, the rapeseed-based biodiesel produced entirely in Spain is the most sustainable alternative of biodiesel, with higher normalized weight (0.398), over soybean-based biodiesel produced in Argentina (0.291) or in Spain (0.312) using soybean oil imported from Argentina, because it could significatively increase job creation and gross value added. Highlights: First-generation biodiesel is a key partial rapid solution to replace petrodiesel. Normalization and weighting can help policymakers to select the best alternative. Climate change followed by human toxicity got the higher weighs (0.380 and 0.177). Spanish biodiesel made with rape oil could increase job and economic performance. Spanish biodiesel made with rape oil is the most sustainable alternative in Spain.